Characteristics of wheeze during histamine-induced airways obstruction in children with asthma. Issue 2 (February 1995) - Rietveld, S; Dooijes, E H; Rijssenbeek-Nouwens, L H; Smit, F; Prins, P J; Kolk, A M; Everaerd, W A
Abstract : BACKGROUND--An automated system has been developed for the detection of sound patterns suggestive of airways obstruction in long term recordings. The first step, presented here, was tracheal sound recording during histamine-induced airways obstruction. METHODS--The tracheal sounds of 29 children aged 8-19 years with asthma were recorded during airways obstruction caused by histamine inhalation using a system for continuous respiratory telemetry and computer analysis. Sound patterns were analysed, classified, and related to airways obstruction measured by lung function tests based on the forced expiratory volume in one second (FEV1). RESULTS--Five sound patterns were identified, one dominant sensitive and four specific to a fall in FEV1 of > 20%. The presence of at least one of three specific sound patterns during unforced respiration predicted a fall in FEV1 of > 20% in 87.5% of the subjects. The inspiratory and expiratory sound patterns were almost equally informative of airways obstruction. CONCLUSIONS--Wheezes can be differentiated with more precision than is currently accepted. Tracheal sound patterns are sensitive and specific predictors of histamine-induced airways obstruction. These patterns are neither invariably nor proportionally related to the results of lung function testing. However, they can be used for detection of airways obstruction on the basis of their presence or absence.